Effect of soil amendments on growth, minerals and proximate composition of Lawmen taraxacifolia (Willd.) Amin Ex C. Jeffrey (2015)
Launaea taraxacifolia is a rarely consumed vegetable in a few countries of Africa where it is cultivated. It is mostly restricted in range to the wild. It is indigenous and largely uncultivated in Nigeria due to cultural inhibition and lack of information on its dietary benefits. Knowledge of its minerals and proximate contents under various soil amendments would enhance its consumption in southwest Nigeria. Field assessment of response of L. taraxacifolia to soil amendments was carried out at Atiba Local government area (LGA), Oyo State, Nigeria in the rainy season of 2015. Number of leaves produced and mean leaf areas (cm2) of Launaea taraxacifolia to poultry manure, cattle dung at the rate of 2 t/ha and urea (200kg/ha) were assessed in a completely randomized design with five replicates. Data were analysed using analysis of variance. Means that were significant were separated using Duncan’s Multiple Range at ¥=§.05.Launaea taraxacifolia performed better on Urea fertilized plots better than in plots supplied other amendments and control. There was no significant difference in number of leaves and leaf area of Launaea taraxacifolia in plots amended with cattle dung or poultry manure. The vegetable had significantly (P<0.05) highest ash (2.30%), fat (2.10%), carbohydrate (77.62%) and energy content (338.38 Kcal/J) in plots amended with cattle dung. The study indicated that the perforamnee of Launaea taraxacifolia under synthetic and organic soil amendments was comparable.